Unemployment and Its Influence on Poverty Level - Probosiwi, Ratih (Jurnal Penelitian Kesejahteraan Sosial, 2018)
Poverty is one of main issue in many discussions in developing countries, including Indonesia. In some previous studies showed that unemployment has significant impact on poverty levels. The case study took the city of Yogyakarta as the region with the highest unemployment rate in Yogyakarta Special Territory (YST) but has the lowest levels of poverty. This paper attempts to reveal the influence of unemployment and poverty in Yogyakarta Municipalities via data in the last ten years. Through statistical analysis, the relationship between unemployment and poverty are tested and be seen to do. The results showed that in fact unemployment and poverty showed no significant effect with significant value 0.159 (greater than Î± 0.05) with directional value. This shows that there is no direct link between unemployment and poverty in the city of Yogyakarta, which can be caused by educated unemployment who are looking for work and are not included in the group of the poor.